The effects of short-term exposure to selected heavy metals carried by airborne fine particles on neural biomarkers during dust storms. Issue 5 (16th October 2020) - Badeenezhad, Ahmad; Baghapour, Mohammad Ali; Azhdarpoor, Abooalfazl; Keshavarz, Mojtaba; Amrane, Abdeltif; Goudarzi, Gholamreza; Hoseini, Mohammad
Abstract: This study aimed to investigate the effects of short-term ambient environmental exposure to fine particles and heavy metals (HMs) on neural biomarkers of people within dust storm conditions. From 44 healthy volunteers, who had already been identified, blood and urine samples were taken 24 h before the dust storm. Their blood and urine samples were taken 24 h after exposure. Vanillylmandelic acid (VMA) and homovanillic acid (HVA) were measured as urine markers, while neuron-specific enolase (NSE), cortisol, S100β, and white blood cells (WBCs) were tracked as blood markers. Eleven HMs (Fe, Mn, Zn, Cr, Co, Al, Ni, Pb, Cd, As, and Cu) correlated with fine particles were measured in both normal and dusty days. The mean concentration of fine particles on normal and dusty days was 60.21 and 238.8 µg m −3, respectively. The mean value of the post-exposure NSE and S100β was 0.59 ng/L −1 ( p  = 0.002) and 5.61 ng/L −1 ( p  ≤ 0.004) higher than that of the pre-exposure respectively. However, the average blood cortisol level decreased by 3.12 ng mL −1 after exposure compared to before it. The mean post-exposure HVA was 0.59 mg g −1 creatinine (CRT) higher than the mean pre-exposure HVA value, which was statistically significant ( p  = 0.000). Ni ( r  = 0.6), Cd ( r  = 0.85), and Fe ( r  = 0.7) caused an increase in the NSE biomarker. Metal compounds and toxicity of fine particles in dust storms may affect biological markers related to nervous system function and systemic physiological stress.